VIOLATION OF ETHICS BY PUBLIC OFFICIALS IN RELATION TO CORRUPTION CASES - Hasanal Mulkan; Reny Okprianti; Serlika Aprita; Ferindi Ramadan Pratama (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The public ethics of state officials in the administration of clean government holds an important position and role as a guide for good behavior in carrying out their duties. The occurrence of political corruption is not solely attributed to the extent of authority possessed but is also rooted in the violation of the ethics of state officials. This study employs qualitative research methods and a literature approach to explore law violations stemming from breaches of state officials' ethics, focusing on the Hambalang Political Corruption case handled by the KPK. The investigation delves into how violations of state officials' ethics transpire, originating from both the executive and legislative branches.The breach of state officials' ethics in this case is linked to the struggle for interests in securing funds to support a candidate for the general chairmanship of a political party. Beyond implicating the executive and legislature, the corruption also involves the private sector. The manipulation of legal loopholes in preparing the APBN is exploited to inflate the value of the Hambalang project, resulting in substantial budgets, profits, and an escalation of corrupted funds. The case study reveals ethical violations by state officials, characterized by dishonest behavior, data manipulation, and a lack of transparency to secure approval for the Hambalang project. These ethical transgressions are coupled with legal violations, ultimately eroding public trust in endeavors to establish a corruption-free government, particularly concerning officials affiliated with political parties.